Terror and its discontents : suspect words in revolutionary France - Weber, Caroline, 1969- (University of Minnesota Press, 2003)
Terror and Its Discontents is a revealing look into the paradoxical embargo on free expression that underpinned the Robespierrists' self-proclaimed "despotism of liberty" during the French Revolution. Caroline Weber provides a highly original--and timely--exposition of the political uses of rhetoric and of the links between language and power